Appetite stimulant before meal aids faster recovery from illness: a comprehensive review - Tiwaskar, Mangesh (International Journal of Research in Medical Sciences, 2025)
Loss of appetite (LOA), or anorexia, is a significant health concern that can arise due to various factors such as age, illness, or medication, leading to nutritional deficiencies and impacting overall health and quality of life. LOA can be categorized as acute or chronic, with the latter often associated with serious underlying conditions, including cancer and chronic diseases. This review explores the multifactorial causes, prevalence, and health consequences of LOA, emphasizing the importance of early diagnosis and intervention. A multi-centre survey conducted in India revealed a striking prevalence of LOA, affecting 93.1% of 15,914 participants, particularly those with infectious diseases. Effective management strategies are critical, with tools like the Council on Nutrition Appetite Questionnaire (CNAQ) aiding in the assessment of appetite. Pharmacological interventions, including appetite stimulants, play a role in enhancing food intake, while the combination of multivitamins, zinc, and lysine has been found to support appetite stimulation and improve nutritional status. Understanding the complex interplay of physiological, psychological, and pharmacological factors is vital in developing standardized guidelines for managing LOA. Increasing awareness regarding early diagnosis and timely management is essential to improve nutritional status and quality of life for affected patients.